Two Cases of Cartilaginous Choristoma—Not Chondroma of the Bony External Auditory Canal - Kohei Yamahara; Yuki Katsura; Yuki Egawa; Kana Lee; Satoshi Ikegami (Case Reports in Otolaryngology)
The presence of a cartilaginous mass on the bony external auditory canal is an unusual finding. Currently, two different diagnoses have been used to describe this type of mass: chondroma and cartilaginous choristoma. There is currently no consensus on which diagnosis is appropriate for this type of lesion. Choristoma is defined as a tumor-like growth of normal tissue occurring in an abnormal location. Histological examination alone cannot be used to distinguish between cartilaginous choristoma and chondroma, as both lesions comprise normal mature hyaline cartilage. To diagnose a mass as cartilaginous choristoma on the bony external auditory canal, it is necessary to confirm that it does not originate from the underlying periosteum. Here, we present the cases of two patients with typical cartilaginous masses on the bony external auditory canal, in which the surgical findings showed that the masses were not in contact with the underlying periosteum, indicating that cartilaginous choristoma—not chondroma—is an appropriate diagnosis for these mass lesions. The clinical findings (characteristic appearance and location) reported here may aid clinicians in the diagnostic and surgical management of these cartilaginous masses.